Fluorescence Quenching Investigation of Methyl Red Adsorption on Aluminum-Based Metal-Organic Frameworks - Chen, Jun-Kai (Langmuir : the ACS journal of surfaces and colloids, 2018)
The adsorption of methyl red (MR) isomers (ortho, meta, and para) on metal-organic frameworks (MOFs) was investigated by using a fluorescence quenching technique. All three MR isomers were found to quench the fluorescence of MOFs effectively. Nonlinear fluorescence quenching trends were observed in Stern-Volmer plots. A modified nonlinear Stern-Volmer equation with the concepts of multiple adsorption sites, adsorption strength, and quencher accessibility was successfully adopted to fit the fluorescence quenching data. The fitted parameters were correlated with the structural properties of MRs and MOFs. The order of quenching efficiency was found to be m-MR > p-MR > o-MR for all MOFs. This indicates that MR molecules not only adsorb via carboxylate-metal bonding but also adsorb through π-π interactions between the aromatic rings of MR and linker molecules in MOFs. The position of the carboxylate group in MRs and the structure of the linkers in MOFs are the key factors affecting the fluorescence quenching efficiency